2005
DOI: 10.1007/s00240-005-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

Complications of the upper urinary tract in patients with spinal cord injury: a long-term follow-up study

Abstract: The aim of this study was to establish hazard ratios for the risk of complications of the upper urinary tract in relation to bladder management methods in patients with spinal cord injury. A total of 179 male patients were eligible for this investigation which was followed-up on a yearly basis until 2003. The average age at which the lesion occurred was 25.2 years (range 18-57). The average duration of follow-up since SCI was 29.3 years (range 10-53). During follow-up, the incidence of vesicoureteral reflux (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 11 publications
2
34
1
4
Order By: Relevance
“…The bladder management method has been reported to have no effect on renal calculi formation. 8,15 Bartel et al 5 noted bladder calculi by IUC in 6.6% and by CIC in 2%. Chen et al 14 found that IUC was associated with a substantially greater risk of bladder calculi; however, Ku et al 12 did not show this relationship with bladder calculi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bladder management method has been reported to have no effect on renal calculi formation. 8,15 Bartel et al 5 noted bladder calculi by IUC in 6.6% and by CIC in 2%. Chen et al 14 found that IUC was associated with a substantially greater risk of bladder calculi; however, Ku et al 12 did not show this relationship with bladder calculi.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The principle aim of managing LUT dysfunction is the prevention of complications and preservation of upper urinary tract function. 1,[6][7][8] Therefore, these patients need life-long urological assessment at regular intervals to minimize urinary tract-associated morbidity. [6][7][8] Although there is no agreed protocol for the follow-up procedure, ultrasound (US) has an important role in the urinary tract surveillance of SCI patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doing so, it is evident that intermittent catheterization is superior to indwelling catheters of any kind. [2][3][4] In this case, no misunderstanding about the status of indwelling catheters in the treatment of patients with neurogenic bladder dysfunction due to spinal cord injury would have been possible.…”
mentioning
confidence: 91%
“…Among the most common urinary catheter complications are: anaphylaxis (allergic reaction to latex), cytotoxicity and hypersensitivity [37 40], symptomatic bacterial infection [19,41 51], catheter blockage (due to calculi and encrustations) [52 60], catheter fracture and malignancy [61], hematuria (blood in urine) [ 52,59, 62 64], intravesical knotting [4, 65 67], inflammation (due to pyelonephritis and epididymitis) [44,56,[58][59]62,68], erosion and periurethral abscess [56,59,62], mechanical trauma (partial damage, perforation and urinary leakage) [11 12, 52, 55, 69 73], urethral fistulae [59,62], urethral stenosis and stricture [56,62,72], and urosepsis [62 63, 74 76]. While several studies have investigated the morbidity and mortality associated with urinary catheters [52,62], to date no comprehensive review has been performed which has focused specifically on identifying and analyzing important complications caused or exacerbated by the mechanical interaction (i.e., physical contact) between the catheter and urinary tract.…”
Section: Introductionmentioning
confidence: 99%